Army of darkness [videorecording (DVD)] - Raimi, Sam; Raimi, Sam; Campbell, Bruce, 1958-; Davidtz, Embeth, 1966- (Universal Studios Home Video, 2009)
"Forced to lead a makeshift Dark Ages army against the demonic Deadites, who posses all the deadly magic of Hell, the shot-gun toting, chainsaw-armed, reluctant 20th century time traveler Ash must save the living from the dead, rescue his medieval girlfriend, and get back to his own time"--Container.